Estudio de almacenamiento de una bebida refrescante a partir del mucílago de la hoja de Tuna (opuntia ficus indica). - Loachamin Jacho, Johnny Matias (2022)
Into the current research, it was performed a refreshing drink formulation based on the prickly pear leaf mucilage extract (Opuntia ficus indica), what is delicious in fiber, calcium and A, B and C vitamins, besides to getting therapeutic properties. It was performed the mucilage characterization and the study of the elaborated drink storage. The used methodology was a completely randomized design (DCA) into factorial arrangement A*B with 3 repetitions, by having as study factors the mucilage percentage (20%, 30% and 40%) and the storage temperature (ambient 21° C and refrigeration 4°C), by taking as quality parameters the physical-chemical aspects (Acidity, pH and °Brix) and microbiological (total coliform count, fecal coliform count, molds and yeasts) for the drink elaboration. Once, it was performed the drinks with the different mixtures (water-mucilage), preservatives (citric acid, sodium benzoate, sodium citrate and CMC), sweetener (sucrose) and artificial green apple flavoring, with the indicated percentages were performed the acceptability tests, the drink with the highest acceptance, after, analyzing the variables (Acidity, pH and °Brix), it was determined the best treatment, whose was the 40% mucilage one composed at a 4°C refrigeration temperature. From this formulation, it was made the analyzes, what show valuable functional consideration results. For ensuring the product safety, it carried the physical-chemical and microbiological analyzes required by NTE INEN 2304 for soft drinks or non-carbonated beverages. The got parameters and specifications met the produced beverage specifications. The beverage storage study was performed, through a conservation process comparison, applying two different treatments, where it is observed that one better preserves its physical-chemical characteristics over time and the other presents a degradation fastest these characteristics.